1993
DOI: 10.1063/1.464735
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yields for OH production from 193 and 248 nm photolysis of HNO3 and H2O2

Abstract: Laser photolysis of HNO3 at 222 nm: Direct determination of the primary quantum yield of OH The absolute quantum yields (ct» for OH production from 193 and 248 nm photolysis of HN0 3 and H 2 0 2 are measured at room temperature using flash kinetic spectroscopy in a flow tube. The OH radicals are produced by excimer laser photolysis and probed via direct absorption of high resolution, tunable IR laser light. The resulting quantum yields are found to be <1>~~03 = 0.47 ± 0.06, <1>~i~2 = 1.22 ± 0.13, <1>:0 3 = 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 44 publications
4
38
0
Order By: Relevance
“…The negligibly small value obtained for H (240) is consistent with the previous report that the quantum yield for OH formation is 2, and the yield for H atom formation is less than 0.0002 at 248 nm [6]. On the other hand, Schiffman et al [8] suggested that the quantum yield for OH formation at 248 nm is smaller than 2, and that other product channels should open. Our results imply that the H atom formation channel (5) is not attributed to the other product channels other than the OH formation at 248 nm.…”
Section: Resultssupporting
confidence: 87%
“…The negligibly small value obtained for H (240) is consistent with the previous report that the quantum yield for OH formation is 2, and the yield for H atom formation is less than 0.0002 at 248 nm [6]. On the other hand, Schiffman et al [8] suggested that the quantum yield for OH formation at 248 nm is smaller than 2, and that other product channels should open. Our results imply that the H atom formation channel (5) is not attributed to the other product channels other than the OH formation at 248 nm.…”
Section: Resultssupporting
confidence: 87%
“…This high production of oxygen atoms was believed to be a manifestation of a decay path different from pathway (1), most likely a decay channel leading to the products HONO + O. Almost parallel to this study, Schiffman et al [30] also measured the OH yield. They monitored the time-resolved IR absorption of this fragment after laser flash photolysis at 248 and 193 nm.…”
Section: Determination Of Quantum Yieldsmentioning
confidence: 83%
“…The rate constants measured from earlier experimental work on the kinetics of the H-abstraction from H 2 O 2 are shown in Table V [7,[42][43][44][45][46][47][48]. The calculated rate constant including ZPE with quantum tunneling at room temperature for H-abstraction reactions from H 2 O 2 is shown in Table VI.…”
Section: Bond Dissociation Energy and Scaling Of Correlation Energymentioning
confidence: 97%